Towards a general subtraction formula for NNLO QCD corrections to processes at hadron colliders: final states with quarks and gluons - Federica Devoto; Kirill Melnikov; Raoul Röntsch; Chiara Signorile-Signorile; Davide Maria Tagliabue; Matteo Tresoldi (Journal of High Energy Physics)
Abstract We describe the calculation of integrated subtraction terms in the nested soft-collinear subtraction scheme for hadron collider processes with quarks and gluons, thereby extending the results presented in ref. [1]. Although this extension eventually proves to be straightforward, it requires a more careful treatment of certain collinear limits to achieve a compact and physically-transparent final result. We also show that the cancellation of infrared divergences can be organized in such a way that, once soft contributions are removed, it occurs independently for each of the external partons. We consider these results to be important stepping stones on the way to deriving finite remainders of the integrated subtraction terms for fully-general hadron collider processes in the context of the nested soft-collinear subtraction scheme.